Cobalamin deficiency and pathogenesis of neurological disorders - A. V. Pereshein; S. V. Kuznetsova; T. E. Potemina (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
The brief review deals with the specific value of B vitamins for the nervous system, the mechanisms of transport and metabolic functions of cobalamin, pathogenetic theories related to vitamin B12 deficiency such as canonical biochemical theory and the theory of dysregulation of cytokines and growth factors; the hyperhomocysteinemic component of cerebral small vessel disease as one of the most common types of degenerative disorders of the central nervous system has been mentioned; the types of disorders associated with cobalamin deficiency that underlie its neurological manifestations have been described.